2017
DOI: 10.1021/acs.jnatprod.7b00008
|View full text |Cite
|
Sign up to set email alerts
|

Concise Syntheses of Hyrtioreticulins C and D via a C-4 Pictet–Spengler Reaction: Revised Signs of Specific Rotations

Abstract: The first syntheses of hyrtioreticulins C and D via a Pictet-Spengler reaction at the C-4 position of the indole rings are described. The synthesis proceeds in only two steps from commercially available starting materials. In this Communication, the structures of the natural products were confirmed. Furthermore, we revise the signs of the specific rotations of hyrtioreticulins C and D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…497 The absolute congurations of purpuroine A 1214 and nakirodin A 1215 have been revised following their synthesis, 498 while spiroleucettadine 499 and both madangamines C and E 500 have been made. Similarly, the signs of the specic rotation for natural hyrtioreticulins C and D have been reversed following their synthesis, 501 while the structure of topsentin C has also been revised to 1216 some 37 years aer its initial report. 502 A large number of indole-containing alkaloids have been synthesised including makaluvamine O and batzelline D, 503 dictyodendrin G, 504 leucettamine C, 505 isonaamidine E, 506 and cylindradine B, 507 while both enantiomers of the bromotyrosine itampolin A have been produced.…”
Section: Spongesmentioning
confidence: 99%
“…497 The absolute congurations of purpuroine A 1214 and nakirodin A 1215 have been revised following their synthesis, 498 while spiroleucettadine 499 and both madangamines C and E 500 have been made. Similarly, the signs of the specic rotation for natural hyrtioreticulins C and D have been reversed following their synthesis, 501 while the structure of topsentin C has also been revised to 1216 some 37 years aer its initial report. 502 A large number of indole-containing alkaloids have been synthesised including makaluvamine O and batzelline D, 503 dictyodendrin G, 504 leucettamine C, 505 isonaamidine E, 506 and cylindradine B, 507 while both enantiomers of the bromotyrosine itampolin A have been produced.…”
Section: Spongesmentioning
confidence: 99%
“…7 Recently, we reported the first synthesis of the azepinoindole alkaloid hyrtioreticulins C and D through a base-promoted C-4 Pictet-Spengler reaction between tryptophan and acetaldehyde. 8 Although these results demonstrated that such a biomimetic cascade toward hyrtiazepines was possible, there were a few challenges in the synthesis of these alkaloids. To obtain azepinoindoles from the C-4 Pictet-Spengler reaction, the reaction with tryptophan and 5-hydroxyindole-3-carbaldehyde must proceed smoothly.…”
Section: Special Topic Syn Thesismentioning
confidence: 97%
“…However, in the preliminary experiments, this scenario would not be easy to achieve under the previously reported conditions. [6][7][8] Therefore, alternative and appropriate reaction conditions for the C-4 Pictet-Spengler reaction would be necessary to supply a common hyrtiazepine core structure. As an outgrowth of our investigations in the area of indole alkaloids, 9 we envisioned that the C-4 Pictet-Spengler reaction of tryptophans with 5-hydroxyindole-3-carbaldehydes would allow a concise approach to these alkaloids under new reaction conditions.…”
Section: Special Topic Syn Thesismentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 8 a features a complex fused seven‐membered ring and, not being able to obtain suitable crystals, its structure was secured by microcrystal electron diffraction [25] (Scheme 1 B). This cyclization mode is unprecedented in unbiased indole systems, as PS and other electrophilic processes prefer position C2, [26] whereas reactions on position C4 only occur under enzymatic catalysis [27] . Presumably, the coordination with one imidazole N atom in the imine 5 a favors the later cyclization by increasing the steric bulk around C2.…”
Section: Figurementioning
confidence: 99%